Reinventing the Left in the global South the politics of the possible - Sandbrook, Richard (Cambridge University Press, 2014)
"This book offers a fresh appraisal of the nature and significance of the democratic left in the Global South. The moral and intellectual leadership of the left is shifting south from its European birthplace. It is in the Global South, and most notably in Latin America, that one finds newly self-confident progressive movements. This 'new' democratic left includes parties and social movements that not only are avoiding the familiar pitfalls that ensnared socialists and social democrats in the twentieth century, but also are coping with the realities of the twenty-first century, especially neoliberal globalization. In analyzing and illustrating three innovative strategies - moderate social democracy, radical social-democratic transition to socialism, and Left populism - this study nudges the debate about the Left out of the well-worn grooves into which it has fallen in recent decades"--Provided by publisher.